Memorandum of understanding between Universiti Teknologi MARA and Tateyama Food Industries (M) Sdn. Bhd. / Fakulti Pengurusan Hotel & Pelancongan - Universiti Teknologi MARA, Fakulti Pengurusan Hotel & Pelancongan (Universiti Teknologi MARA (UiTM), 2021)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.